Friends on the Margins. Issue 1 (19th February 2019) - Omer, Atalia
Abstract: In this essay, I examine Richard Miller's exposition of political solidarity as one of the key contributions of his multifaceted argument in Friends and Other Strangers to the study of religion, ethics, and culture. Miller's focus on culture broadens the landscape of ethical analysis in ways that illuminate how culture and cultural productions mediate and construct norms and virtues, and the complex relations between self and society. I challenge Miller's inclination, however, to focus scholarly attention more on habituated forms of civic identity and communal solidarity rather than on disruptive potentialities and critical practices. I suggest that an engagement with social movement theory and the sociology of emotions, with their focus on semiotic analysis and social change processes and mechanisms, can greatly enrich Miller's account of religion and ethical solidarity.